Retrospective Study : Rosacea Profile - Shakti Indraprasta; Trisniartami Setyaningrum (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: Rosacea is a chronic skin disorder which characterized by erythema of the central face that has persisted for months. Primary features of rosacea include flushing, papules, pustules, and telangiectatic. Although rosacea is clearly visible to all, it is largely unknown to misunderstood by the general public. Knowledge relating to the epidemiology, etiology, pathogenesis, and treatment of this facial disorder is limited. Purpose: To evaluate the management of patients with Rosacea in the cosmetic division, dermatovenereology outpatient clinic Dr. Soetomo general hospital period 2010-2012. Methods: Retrospective study of new patients with Rosacea in cosmetic division during 2010-2012. Results: During the period of three years (2010-2012), there were 49 new patients in cosmetic division, dermatovenereology outpatient clinic Dr. Soetomo general hospital. The most common patient was female, with the highest age group of 25-44 years old, and the most clinical feature found were papulopustular rosacea and erythemato-telangiectatic rosacea. The most common treatment were metronidazole for topical treatment and doxycycline for systemic treatment. Conclusions: The most clinical feature were papulopustular and erythematotelangiectatic subtype, only few cases of phymatous subtype, while the ocular subtype was not found. There were so many varieties in the management of rosacea because there was no standard therapy yet for the management of this disease.Key words: rosacea, retrospective study, rosacea subtype.